Factors influencing incomplete immunization among under five years old children at CHUK hospital, Nyarugenge district, Rwanda - Nwankwo, Chinenye Mercy; Orua, Elizabeth (International Journal Of Community Medicine And Public Health, 2020)
Background: Low-income countries still have challenges with vaccine-preventable diseases, despite improvement in immunization coverage in Rwanda, cases of drop out and incomplete immunization persists. Methods: The study adopted descriptive cross-sectional approach with the use of quantitative and qualitative techniques on a population of 186 guardians/mothers with their under five children. Convenience sampling techniques was used to draw study sample size of 127 that attends the clinic and approval to participate in the study. Data was obtained from validated study instruments and immunization records over a period of one month. Results: Study results showed that religion (p=0.01), gender (p=0.03), age (p=0.009) and educational status (p=0.04) influenced incomplete immunizations. About 78 (61.4%) respondents are unaware that vaccines prevents specific diseases, while 61 (48.0%) were too busy with other duty at the time of immunizations and 89 (70.1%) Participants do not see the need to complete the immunization. Furthermore, the age of the mother Knowledge of child immunization and hospital delivery were statistically significant with (p<0.05). Immunization cards and histories verified showed about 120 (94.4%) children were fully immunized, 46(24.5 %) were partially immunized and 67 (52.8%) children immunized before age one. Conclusions: A number of children were not fully immunized in their first year of life; others were inappropriately vaccinated. Emphasis made on completion of immunization schedule.